Acylative Coupling of Amine and Indole Using Chloroform as a Carbonyl Group. Issue 29 (10th July 2018) - Nishida, Yuika; Takeda, Norihiko; Matsuno, Kenji; Miyata, Okiko; Ueda, Masafumi
Abstract : Chloroform‐mediated acylative coupling of amines with indoles has been developed. When indoles and amines in chloroform were treated with dimethylzinc in the presence of air, the three‐component aminocarbonylation reaction proceeded via in‐situ generation of phosgene from chloroform and O2 to provide indole‐3‐carboxamides in a single operation. Application to the synthesis of biologically active compounds and intramolecular acylation are also described. Abstract : Chloroform‐mediated acylative coupling of amines and indoles has been developed. Indoles and amines in chloroform were treated with dimethylzinc in the presence of air, resulting in a three‐component acylative coupling reaction in which in‐situ generation of phosgene produces indole‐3‐carboxamides.